Zombies vs. Anxiety: An Augmentation Study of Prescribed Video Game Play Compared to Medication in Reducing Anxiety Symptoms. (October 2018) - Fish, Matthew T.; Russoniello, Carmen V.; O'Brien, Kevin
Objective .Anxiety is a typical reaction to stress and when uncontrolled, clinical anxiety disorders may develop. Traditional anxiety interventions have established efficacy; however, they are often costly and stigmatizing. This study examinedprescribed casual video game (CVG) play added to anSSRI prescription in reducing symptoms of anxietycompared to a two-medication treatment group . Materials and methods . We used data from a larger study examining depression and CVGs. The Quick Inventory of Depressive Symptomology screened participants for depression using a score of ≥ 5 (mild depression). Participants chose to participate in the alternative (n = 30) or traditional (n = 24) group.Alternative group participants were prescribed CVG play four times per week for 30-45 minutes over a one-month period.Traditional intervention group participants were prescribed a second medication . TheState-Trait Anxiety Inventory was used to test hypotheses. Results . Repeated-measures ANOVA demonstrated asignificant decrease in state anxiety scores after the one-month prescription and amedium to large effect for the alternative group.Trait anxiety results did not demonstrate significance; however, the group had amedium effect size . Conclusion . Clinicians should consider thesenon-stigmatizing and low-cost CVGs as afeasible intervention for patients who wish not to take additional medication.